Assessment of Goat Management Practices in the Southern Transition Zone of Hassan District, Karnataka, India - Niteesh Patel B N; Guruprasad R; Jaishankar N; Jagadeeswary V; Shivakumar M C (Archives of Current Research International, 2025)
Arkalgudu Taluk, situated in the Southern Transition Zone of Hassan district, Karnataka, is a prominent goat-rearing region, with goats constituting 35.81% of the livestock population. This study aimed to assess goat management and marketing practices across four villages in the taluk, involving 100 goat farmers with flock sizes of 20 or more. Data were collected via structured interviews and analyzed using IBM SPSS software. Results revealed that, goat housing predominantly consisted of kutcha, closed sheds with earthen floors and asbestos or thatch roofing, mostly located within household compounds. Ventilation was generally inadequate, reflecting limited awareness and financial constraints. Feeding practices relied heavily on community grazing lands (82%) and natural water sources (74%), with most farmers watering goats once daily. Colostrum feeding was timely in most cases, with 64% of kids receiving colostrum within 30 minutes of birth. Solid feeds and green fodder were introduced between 1 and 2 months, supporting early growth. Breeding was mainly uncontrolled natural mating, with farmers maintaining their own bucks at recommended buck-to-doe ratios. Artificial insemination adoption was minimal despite government support. Health management showed moderate vaccination coverage, especially for Haemorrhagic Septicaemia, and regular deworming practices, supplemented by Ethno-Veterinary treatments. Waste management involved composting manure, primarily used as fertilizer in agricultural fields. Overall, a semi-intensive rearing system prevailed with established weaning and castration practices. While traditional management practices dominated, awareness of scientific methods was evident in areas like health care and breeding. The study highlights the importance of integrating improved housing, feeding, and breeding strategies to enhance goat productivity in the Southern Transition Zone of Hassan district.